Reorienting job crafting research: A hierarchical structure of job crafting concepts and integrative review - Zhang, Fangfang; Parker, Sharon (WILEY, 2019)
© 2018 John Wiley & Sons, Ltd. Two dominant perspectives of job crafting—the original theory from Wrzesniewski and Dutton (2001) and the job demands resources perspective from Tims, Bakker, and Derks (2012)—remain separate in research. To synthesize these perspectives, we propose a three-level hierarchical structure of job crafting, and we identify the aggregate/superordinate nature of each major job crafting construct. The first level of the structure is job crafting orientation, or approach versus avoidance crafting, which we argue is an essential yet often neglected distinction in the literature. We address the debate surrounding cognitive crafting and identify crafting form (behavioral versus cognitive crafting) as the next hierarchical level of constructs. Finally, we concur that job resources and job demands, or crafting content, capture different ways that individuals craft their jobs. Using this integrated hierarchical structure, we were able to review antecedents and outcomes from both perspectives. We show, for example, that approach crafting in its behavioral form is very similar to other proactive behaviors in the way it functions, suggesting a need for closer synthesis with the broader proactive literature, whereas avoidance crafting appears to be less proactive and often dysfunctional. On the basis of our review, we develop a road map for future research.